The acute asymmetric effects of hemiovariectomy on testosterone secretion vary along the estrous cycle. The participation of the cholinergic system - Chavira Roberto; Barco Ana I; Meléndez Griselda; Palafox María T; Rodríguez Jorge O; Flores Angélica; Esther Cruz M; Domínguez Roberto (BMC, 2006)
Abstract The presence of asymmetry in the capacity of the left and right ovaries to secrete testosterone was analyzed by studying the effects of hemiovariectomy along the estrus cycle one hour after surgery. The effects of ether anesthesia on hormone serum levels were also analyzed. Bilateral ovariectomy and the extirpation of the left ovary performed on the day of proestrus resulted in significantly lower testosterone levels. Compared to the anesthetized group, the effects of perforating the peritoneum unilaterally varied according to the day of the estrous cycle and the side of the peritoneum surgery was performed on. Injecting atropine sulfate (ATR) to control or anesthetized rats on D1 resulted in a significant increase of testosterone serum levels. The effects of perforating the peritoneum on testosterone levels depended on the cholinergic innervation and varied along the estrous cycle. Blocking the cholinergic system before performing unilateral or bilateral ovariectomy had different effects depending on the day of the estrous cycle. Testosterone plasma levels increased significantly when surgery was performed on the day of diestrus and dropped when surgery was performed on proestrus. Similar effects were observed when the left adrenal was extirpated from animals with the cholinergic system blocked. The results presented herein support the hypothesis of asymmetry in the ovaries' abilities to secrete steroid hormones, and that the capacity to secrete testosterone varies along the estrous cycle.